2012
DOI: 10.1186/1556-276x-7-418
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles administered to chicken affect VEGFA and FGF2 gene expression in breast muscle and heart

Abstract: Nanoparticles of colloidal silver (AgNano) can influence gene expression. Concerning trials of AgNano application in poultry nutrition, it is useful to reveal whether they affect the expression of genes crucial for bird development. AgNano were administered to broiler chickens as a water solution in two concentrations (10 and 20 ppm). After dissection of the birds, breast muscles and hearts were collected. Gene expression of FGF2 and VEGFA on the mRNA and protein levels were evaluated using quantitative polyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…However these are the major segments of the gastrointestinal tract (GI) that are responsible for the digestion and absorption of feed ingredients and nutrients, which may explain why the internal organs' measurements were used in this experiment. Recently published data indicated that Ag-nanoparticles affected gene expression for muscle growth directly or indirectly, fibroblast growth factor 2 (FGF2), vascular endothelial growth factor (VEGF) and Na + /K + transporting ATPase (Hotowy et al 2012;Sawors et al 2013), which may explain the positive effect of nanoclay minerals used in the present experiment, as this clay contains several minerals in its composition such as Na + , K + and Ca ++ , which can enhance internal organs' percentage and increase BW and BWG obtained from our experiment but with nanoclay minerals. Mushtaq et al (2014) demonstrated that Na + , the principal cation of extracellular fluid, is involved in numerous functions including the regulation of acid base balance and the absorption of glucose and amino acids that also play a particular role in improving internal organs' percentage when it is transferred into nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…However these are the major segments of the gastrointestinal tract (GI) that are responsible for the digestion and absorption of feed ingredients and nutrients, which may explain why the internal organs' measurements were used in this experiment. Recently published data indicated that Ag-nanoparticles affected gene expression for muscle growth directly or indirectly, fibroblast growth factor 2 (FGF2), vascular endothelial growth factor (VEGF) and Na + /K + transporting ATPase (Hotowy et al 2012;Sawors et al 2013), which may explain the positive effect of nanoclay minerals used in the present experiment, as this clay contains several minerals in its composition such as Na + , K + and Ca ++ , which can enhance internal organs' percentage and increase BW and BWG obtained from our experiment but with nanoclay minerals. Mushtaq et al (2014) demonstrated that Na + , the principal cation of extracellular fluid, is involved in numerous functions including the regulation of acid base balance and the absorption of glucose and amino acids that also play a particular role in improving internal organs' percentage when it is transferred into nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the NPs induced a reduction in myocardial contractility and augmented the internal diameter of left ventricle, accompanied by changes in the left ventricular internal diameter at the end of diastole (LVIDd), the left ventricular internal diameter at the end of systole (LVIDs), the ejection fraction (EF), the stroke volume (SV), and so forth. Another study on growing chickens indicated that 20 mg/L Ag NPs decreased the expression of fibroblast growth factor 2 (FGF2) and increased the expression of vascular endothelial growth factor A (VEGFA) at both the mRNA and protein levels in the heart and breast muscle . Intriguingly, up‐regulated expression of FGF2 at the transcriptional and translational levels, and increased blood vessel size, cartilage collagen fibre lattice size and bundle thickness in the Ag NP‐treated chicken embryos were recently reported .…”
Section: Bio‐toxicitymentioning
confidence: 96%
“…Another study on growing chickens indicated that 20 mg/L Ag NPs decreased the expression of fibroblast growth factor 2 (FGF2) and increased the expression of vascular endothelial growth factor A (VEGFA) at both the mRNA and protein levels in the heart and breast muscle. 54 Intriguingly, up-regulated expression of FGF2 at the transcriptional and translational levels, and increased blood vessel size, cartilage collagen fibre lattice size and bundle thickness in the Ag NP-treated chicken embryos were recently reported. 55 FGF2 isoforms are essential in many cardiac pathological conditions, such as cardiac hypertrophy, ischemia-reperfusion injury and AS.…”
Section: Bio-toxicitymentioning
confidence: 98%
“…Moreover, stated that nanoparticles have a surface area much larger than microparticles, and as the size of the nanoparticles decreases, the surface area for chemical reactions increases, (reactivity increases 1000 times) which may improve the digestion and absorption of the minerals, and result in the improved growth performance and carcass characteristics of broiler chickens [12]. Furthermore, in more recent studies and indicated that nanotechnology affected the expression of genes directly or indirectly responsible for muscle development and Fibroblast Growth Factor 2 (FGF2), which may also explain the improvement in carcass characteristics when an ANS of clay minerals are used [15,16]. In another recent study, reported that the potential applications of nanotechnology in potential and mechanism of nanotechnology in the broiler industry requires more research to gather sufficient knowledge in this field [4].…”
Section: Carcass Characteristicsmentioning
confidence: 99%